2017
DOI: 10.3168/jds.2016-11834
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment of metritis in dairy cows—A meta-analysis

Abstract: The objective of this meta-analysis was to assess the efficacy of the treatment of bovine metritis with common antibiotic and nonantibiotic treatment options. Acute puerperal metritis, a systemic and potentially painful illness with rectal temperature >39.5°C and signs of toxemia due to an infection of the uterus, occurs within 21 d after parturition. Because of the infectious nature, antibiotics are considered beneficial for the treatment of acute puerperal metritis. Each use of an antimicrobial drug, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 52 publications
(80 reference statements)
1
36
0
6
Order By: Relevance
“…Most of the randomized clinical trials that assessed the efficacy of ATB usage for the treatment of PM reported in the liter ature during the last 2 decades have the advantage of comparing an untreated group or positive control group but have the limita tion of including a limited number of animals [25]. For example, in a recent metaanalysis of ATB treatment of metritis in dairy cows, from a total of 26 trials that were evaluated, only 7 trials reported cure rates, and 5 from these 7 trials used ceftiofur for treatment of PM [16]. These researchers were able to include in the meta-anal ysis 828 ceftiofur treated cows and 804 untreated cows and con cluded that they were not able to compare different ATB treatments or the efficacy of ATB versus non-ATB drugs to metritis occurrence at the time of reexamination [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the randomized clinical trials that assessed the efficacy of ATB usage for the treatment of PM reported in the liter ature during the last 2 decades have the advantage of comparing an untreated group or positive control group but have the limita tion of including a limited number of animals [25]. For example, in a recent metaanalysis of ATB treatment of metritis in dairy cows, from a total of 26 trials that were evaluated, only 7 trials reported cure rates, and 5 from these 7 trials used ceftiofur for treatment of PM [16]. These researchers were able to include in the meta-anal ysis 828 ceftiofur treated cows and 804 untreated cows and con cluded that they were not able to compare different ATB treatments or the efficacy of ATB versus non-ATB drugs to metritis occurrence at the time of reexamination [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent metaanalysis of ATB treatment of metritis in dairy cows, from a total of 26 trials that were evaluated, only 7 trials reported cure rates, and 5 from these 7 trials used ceftiofur for treatment of PM [16]. These researchers were able to include in the meta-anal ysis 828 ceftiofur treated cows and 804 untreated cows and con cluded that they were not able to compare different ATB treatments or the efficacy of ATB versus non-ATB drugs to metritis occurrence at the time of reexamination [16]. Conversely, in our study, over 2400 cow records of ATB treatments, clinical cure, milk production, and reproductive efficiency, were retrieved and analyzed to obtain valuable information of efficacy of PM score 3 treatment under field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations